A Global Land Use and Biomass Approach to Reduce Greenhouse Gas Emissions, Fossil Fuel Use and to Preserve Biodiversity - Arthur Riedacker (Fondazione Eni Enrico Mattei (FEEM), 2007)
As average growth consumptions per capita and world population will continue to grow, the promotion of sustainable developments during the next half a century implies to take into account environmental aspects, local potentialities and futures changes in population as well climatic, economic and social factors. At the global level, land and fossil fuel availability per capita, capacity of absorption of greenhouse gas emissions are considered the most important environmental factors. Whereas at local levels are to be considered preservation or improvement of soil fertility, of water regimes, of quality of air, soil and water. Biodiversity must be taken into account at both levels to cope also with climate change. But as underlined by IPCC lead authors, up to now there is no tool available to deal with these issues in a comprehensive and adequate manner. A new tool, presented here, the Integrated Environmental Assessment (IEA) has therefore been developed. It takes into account all actions, from the sun to final services, in three stages: solar energy bioconversion and phytomass production at I; conversion of phytomass and non renewable resources into final products and waste disposal at II ; arrangement of products to meet final needs, such as nutrition, housing mobility etc. at III. IEAs start at the global level with the GIEA , the results of which are then to be confronted with constraints at local levels from LIEAs. This new tool can be used to identify impacts of technological changes in land management and to compare alternative practices better than with LCAs. It was used to analyze environmental impacts of technological changes between 1950 and 2000 in France, in wheat production at stage I. It appeared that not only yields, but also the primary mitigation potential (PMP) per hectare have been multiplied by 4, whereas the net primary energy gain per ha has been multiplied by 3.2. Besides this, 14,5 Mha (the area of the French forest about a quarter of France) land use change could be avoided; in the case of deforestation this would have led to the emission of more than 4 billion tons of CO2. Lessons are drawn from the past and for the next fifty years: In developed and industrialized countries, alternative managements of land and increased use of non food phytomass can and should be envisaged. In Sub-Saharan Africa population is expected to double during the next 50 years and soil fertility is drastically decreasing; agricultural practices are no longer sustainable. If no changes appear in agriculture, forests and GHG emission from deforestation as well as biodiversity are threatened by further and inevitable land use change. Increasing yields per hectare should therefore become the priority; it would at the same time increase food security, improve mitigation and adaptation to climate change, help to combat deforestation and desertification, better preserve biodiversity, and ultimately also allow more bioenergy production: This would improve the food security and at the same time help to achieve the objectives of the three main UN environmental conventions and of the UN Millennium Goal.
Keywords: Q23; Q27; 330; Greenhouse Gas Emission; Fossil Fuel; Biodiversity; Bodennutzung; Bioenergie; Luftverunreinigung; Fossiler Energieträger; Biodiversität; Welt